2021
DOI: 10.3390/ma14174836
|View full text |Cite
|
Sign up to set email alerts
|

Stainless Steel Surface Nitriding in Open Atmosphere Cold Plasma: Improved Mechanical, Corrosion and Wear Resistance Properties

Abstract: This work presents preliminary results regarding improving the mechanical, wear and protective properties (hardness, coefficient of friction, corrosion resistance) of AISI 304 stainless steel surfaces by open atmosphere cold plasma surface treatment method. Comparative evaluations of the morphological, corrosion resistance, mechanical and tribological properties for different periods of treatment (using N2 gas for cold plasma generation in an open atmosphere) were performed. AFM surface analyses have shown sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Instead, in the case of the CrAlN coat, the substrate preparation was found to have no significant impact on its properties. Heat and surface treatments are techniques generally proven to be useful for improving mechanical properties by causing changes to the surface of materials [18]. In summary, steel X39Cr13 is a popular, medical-grade material used for various instruments, including surgical ones [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, in the case of the CrAlN coat, the substrate preparation was found to have no significant impact on its properties. Heat and surface treatments are techniques generally proven to be useful for improving mechanical properties by causing changes to the surface of materials [18]. In summary, steel X39Cr13 is a popular, medical-grade material used for various instruments, including surgical ones [23].…”
Section: Resultsmentioning
confidence: 99%
“…The process was carried out at a temperature of 400-450 • C. The researchers revealed that nitrogen-induced lattice expansion occurs below the nitridecontaining surface layer in Invar 36 alloy after TPN treatment, implying that Cr is not necessary for the nitrogen-interstitial-induced lattice expansion phenomenon to occur also suggesting another type of gamma (N). More and more studies related to nitriding focus on nitriding corrosion-resistant steels [16][17][18][19][20][21]. Lin et al [16] studied plasma-nitrided austenitic stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…Mateescu A.O. et al [61] used cold plasma surface treatment to improve the mechanical, wear and protective properties of the surface of AISI304 stainless steel. The results showed that the surface friction coefficient of the treated material could be reduced to 0.2, the corrosion resistance was improved, and the surface hardness was higher than that of the untreated surface.…”
Section: Ion Implantation Technologymentioning
confidence: 99%
“…As already mentioned, the nitrided sample is characterized by increased surface hardness, increased wear resistance, high fatigue strength, increased corrosion resistance, and high dimensional stability [1,[24][25][26][27][28][29][30][31][32][33][34][35][36][37]. This is possible because a sufficiently high concentration of nitrogen on the steel surface determines the formation of Fe-N phases.…”
Section: Introductionmentioning
confidence: 99%